The Federal Nation
XIV, 265 p. 4 illus.
Keywords: This volume gathers contributors from both the US and UK to provide a comparative examination of federalism in the Bush era, a period of huge change in national politics, but also one of significant shifts in US federalism in relation to social and socioeconomic issues.